RETRACTED: A Microglia Initiated Target Therapy in Neuroinflammation for Alzheimer’s Patients - Bahadur Khan, Faiza; Abedi, Alireza; Olamide Bukola Ogunleye, Andrea; Goderidze, Tamar; Hosseinpour Chermahini, Siavash (Journal of Alzheimers Research and Therapy, 2024)
This article has been retracted on 20 March 2025. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2998-4211.jalr-25-5855) The research is focused on neuroinflammation a normal physiological process which is known to be associated with neurodegenerative diseases could be the potential targeted therapy via the microglia cells, it starts with defining Alzheimer’s; a neurodegenerative disease which causes deposition of Aβ (amyloid beta) protein in the cerebral cortex as well as NFT (neurofibrillary tangles) in the hippocampus and basal ganglia. The paper then describes process of neuroinflammation, microglia’s role, apolipoprotein E4 gene in relation to Alzheimer’s, which leads to different stem cell research and how pruning microglia as well as targeting microglia receptors in the brain is being used in current research trials, we included multiple meta-analysis showing microglia receptors being targeted currently by emerging drugs like propofol, antibodies CSF1R inhibitor etc, which are currently under trial phase, the research ends with concluding potential diagnostic markers like sirt1 considered to be an anti-aging protein which can be used as therapeutic interventions and Lps effect on Sirt 1. A Microglia initiated target therapy in Neuroinflammation for Alzheimer’s Patients.
Keywords: Alzheimer’s disease; Stem cells; Aβ alpha beta PROTEIN; Nft : neurofibrillary tangles; LPS; Lipopolysaccharide